Accessibility in assessment for learning: sharing criteria for success - Willis, Jill; Arnold, Julie; DeLuca, Christopher (Frontiers in Education, 2023)
Assessment for Learning (AfL) practices in secondary schools are intended to help learners understand and what expert performances in disciplines look like, and then apply this understanding to their own learning and assessment performances. Common AfL practices such as sharing criteria for success through rubrics and students using them to interrogate exemplars and give feedback rely heavily on the students’ language and attention. Students need to understand and draw on conceptual and collaborative language, and to make connections across several activity stages. Consequently, students with language and/or attentional difficulties and their teachers face a dilemma. On the one hand, AfL practices can provide access to developmentally appropriate curriculum. On the other, AfL practices may present additional barriers to learning. This article identifies some of the barriers students with language and/or attentional difficulties may encounter in common AfL practices, and how teachers adapted sharing of success criteria to design for greater accessibility. Access to learning is conceptualised by referring to Dewey’s principles of continuity and interaction. Interviews with 20 teachers were analysed to find out how they adapted AfL to be more accessible in an 8 week AfL pedagogical intervention focussed on success criteria. Ideas for designing accessible AfL practices from the outset are outlined as teachers realised the role of their language, small steps, visual tools, and regular opportunities for connection and interactions in making it more likely for students to benefit from AfL practices. Given that students with language and/or attentional difficulties represent some of the highest occurrences of disability in student populations, these ideas have immediate relevance for teachers and those who support AfL practices in educational policy and research.